Managing Phytophthora diseases on ornamentals - Kumar, S Vinod; Senthilraja, C; Nakkeeran, S (Indian Horticulture, 2019)
The ornamental crops are afflicted by a number of diseases. Of them, diseases caused by Phytophthora are of enormous economic importance. They deteriorate the quality of blooms, making flowers/blooms less attractive to consumers. Their timely management is the need of the hour.